2021
DOI: 10.3390/f12070918
|View full text |Cite
|
Sign up to set email alerts
|

Bending Stiffness of Hybrid Wood-Metal Composite Beams: An Experimentally Validated Numerical Model

Abstract: This paper presents an experimentally validated model for the computational analysis of metal-reinforced wooden composites. The model can be used in both research and in industry to effectively estimate how much a certain composite design improves the bending stiffness and strength of a hybrid metal-reinforced wooden component. A model based on computer simulations allows the prediction and analysis of the mechanical behaviour of a hybrid composite material consisting of several interconnected components made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The steel sandwich beam, sometimes called the Flitch beam, is the ancestor of this type of component [29]. This composite beam can also be built with steel sections [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The steel sandwich beam, sometimes called the Flitch beam, is the ancestor of this type of component [29]. This composite beam can also be built with steel sections [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…There are so many properties were available in every material in the world but the desired properties of the individual material were obtained by the various methods of processing [1][2][3][4][5][6][7][8][9]. There are Aluminium is the one of the materials which is desirable due to its low weight and economic cost in current situation [10][11][12][13][14][15][16]. In this investigation main focus on Aluminium alloy of AA8079.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium food waste cans and other used containers recycled and prepared composited with wood particulate composite and included the samples in mechanical and microstructural examinationsand found that significant improvement on mechanical properties [9]. Apart from mechanical properties Wood/metal composites possesses improved decorative values [10], electromagnetic shielding [11] and flame retardancy [12]. Wood metal composites improves structural stability [13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, wood has become an increasingly interesting alternative to steel and concrete due to greater environmental awareness and the general trend towards sustainable construction materials. There are many studies that have investigated different materials and manufacturing processes to develop highly engineered wood products to achieve an increased load-bearing capacity and stiffness [1][2][3][4][5][6]. Products made from biological materials such as wood often exhibit complex mechanical behaviour.…”
Section: Introductionmentioning
confidence: 99%